Reformasi Hukum Pidana Islam: Telaah Nalar Arab Muhammad Abed Al-Jabiri - Lina Nur Anisa (CV. Kalimasada Group, 2025)
The reform of Islamic criminal law in the modern era is an important effort to maintain the relevance of Islamic teachings in addressing dynamic social challenges. This study aims to analyze the reform of Islamic criminal law through a rational-critical approach based on the thoughts of Muhammad Abed Al-Jabiri, focusing on the integration of maqasid shariah principles and modern social contexts. The research employs a qualitative method with a library study approach, including an analysis of primary and secondary literature from Al-Jabiri’s works and other contemporary thinkers. The findings indicate that the main challenges of reform include internal resistance from traditionalist groups and differences in interpretation, as well as external pressures such as negative stigma in the Western world and demands for alignment with human rights standards. The reform of Islamic criminal law holds promising prospects by emphasizing a welfare-oriented approach, the principle of substantive justice, and the active role of academics and educational institutions in supporting change.